EVALUASI KUALITAS WEBSITE UNIVERSITAS MAHAKARYA ASIA KABUPATEN OGAN KOMERING ULU MENGGUNAKAN METODE WEBQUAL 4.0 - Takdir Alisyahbana; Tata Sutabri (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The website has become an essential part of service delivery for a government institution. To determine user satisfaction levels, the quality of a website needs to be measured to serve as an evaluation for website administrators. In this evaluation process, the author utilizes the webqual method and follows government website implementation guidelines. In the data analysis process, the researcher distributes questionnaires using purposive sampling, with a total of 60 respondents, and conducts validity and reliability testing. Subsequently, the questionnaire data is processed based on respondent distribution, yielding a positive response from respondents at a percentage of 54.1%. Furthermore, the website is measured accordingly, resulting in the highest percentage of conformity at 59%.